STOCK RETURN DURING PANDEMIC COVID 19: A COMPARISON BETWEEN INDONESIA AND SINGAPORE STOCK MARKET - Romieo Romieo; Robin Robin; Hesniati Hesniati (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
The purpose of this study is to provide an overview of the stock market conditions of IDX and SGX due to the influence of COVID 19. Through a regression analysis study method to see the condition of stock returns on companies in IDX and SGX. These two countries were taken as the focus of the study considering the closeness of business relationships and the highest number of COVID 19 cases in the Southeast Asia Region. The researcher concludes that the Indonesia Stock Exchange is more sensitive to the increase confirmed case of COVID 19 and the Singapore Stock Market is more sensitive to the increase deaths cases of COVID 19. The conclusion of this study is that the threat of COVID 19 will have a different effect on investor behavior in each country, this could be due to the influence of differences between cultural values and characteristics.